Research on Access Authentication and Re-Authentication Mechanism of User Devices in Terrestrial Default Scenario in Satellite Internet - Qiuyu BU; Jin CAO; Lifu CHENG; Ruhui MA; Hui LI (天地一体化信息网络)
For the current user device access authentication mechanism requires ground participation to bring about large communication delays and poor scalability, a user device access authentication and re-authentication protocol in the ground default scenario in the space-ground integrated network was proposed, and further for the user device authentication process may occur in the power outage reconnection and AV asynchronization and other problems, a user device fast authentication mechanism and AV fast security synchronization mechanism under power failure reconnection scenario were proposed to ensured that users could safely accessed the satellite network and obtain related services.In the proposed scheme, the AV vector generated in the initial access authentication was used to assisted the re-authentication process to completed the authentication between entities without the involvement of the network control center, which guaranteed the communication system resilience.The formal verification tool Scyther showed that the proposed protocol was resistant to common protocol attacks, guaranteed the confidentiality and integrity of the communication process, and had a small signaling, computational, and bandwidth overhead, made it suitable for the satellite internet.